KARAKTERISTIK EDIBLE FILM DARI EKSTRAK KACANG KEDELAI DENGAN PENAMBAHAN TEPUNG TAPIOKA DAN GLISEROL SEBAGAI BAHAN PENGEMAS MAKANAN - Loisa Lorensia Sinaga, Melisa Seri Rejekina S, Mersi Suriani Sinaga (Jurnal Teknik Kimia USU, 2013)
One way to solve the environment issue in the usage of nonbiodegradable plastic is by using biodegradable packaging. Edible film is a thin layer which is overlay the food. In this research, edible film made from mixture of soybean extract with starch and glycerol. The process of making edible films is began with producing soybean protein extract producing soy milk. Soy milk added by tapioca flour and glyserol variations : 2; 4; 6; 8 and 10 (ml/100 ml soy milk). Then, the mixture stirred by using magnetic stirer, formed and dried in the oven at the temperature of 40 °C ± 2 days. After that, the characteristics test of edible film done by checking the thickness, the tensile strength and elongation at break. The results of research shows that the addition of glycerol influence the edible film’s thickness, tensile strength and elongation at break. The thickness obtained from the increasing of the addition glycerol. They are 0,208 mm; 0,228 mm; 0,248 mm; 0,274 mm and 0,294 mm. The tensile strength will decrease if the thickness of the edible film increase. They are 0,105 MPa; 0,134 MPa; 0,088 MPa; 0,072 MPa and 0,048 MPa. The elongation at break which is obtained will increase by increasing of edible film’s thickness. They are 1,839%; 3,270%; 3,842%; 5,779%, and 6,158%. The characteristic’s test shows that the best thickness of edible film is 0,228 mm.